Penggunaan Model Pembelajaran Discovery Learning Pada Pembalajaran Matematika Sebagai Upaya Meningkatkan Hasil Belajar Peserta Didik di Kelas VI SDN 03/X Tanjung Solok Semester Genap Tahun Ajaran 2020/2021 - Aida Susana (Journal on Education, 2022)
This study aims to describe and obtain information on improving Mathematics learning outcomes through Discovery Learning. This research is classroom action research consisting of two cycles, each cycle consisting of two meetings. Each meeting consists of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were students of class VI SDN 03/X Tanjung Solok, totaling 27 people. This research was conducted in the even semester of the 2020/2021 academic year. Data collection techniques using tests, observations, and documentation. Data were analyzed using percentages. The results of the study indicate that through Discovery Learning can improve the mathematics learning outcomes of class VI students at SDN 03/X Tanjung Solok by giving praise.